A Study on the Role of Economic and Institutional Environment on the Corporate Responsibility Performance and its Synchronization - Jong-Hee Kim (East Asian Economic Review)
This paper analyzed how the country’s institutional and political environment affect ESG performance of the companies in the country. An empirical analysis of this study results are as follows. First, the clear difference in financial variables such as the growth rate of foreign direct investment, pension fund assets to GDP ratio, and stock market return rate was found to the significance between advanced economies and emerging markets. Second, in two groups, the institutional indexes, which refer to government policy and the country’s institutional environment such as the rule of law, the government effectiveness, corruption control, and citizens’ voice and accountability showed a positive relationship with ESG performance of the companies. They had a particularly large positive effect on the companies in emerging markets. And third, companies’ synchronization with other companies’ high ESG performance had a positive effect on their ESG performance, and such a tendency was much stronger in the companies of emerging markets. Additionally, institutional dimension had a positive effect on the companies’ synchronization, and such a tendency was much stronger in emerging markets.